Results out on application to varsities - New Straits Times, (2012)
KUALA LUMPUR: The status of applications to Universiti Malaya (UM) and Universiti Kebangsaan Malaysia (UKM) for the Sijil Pelajaran Malaysia (SPM)graduate study prosramme, or its equivalent, has been Josted.